The Relationship Between Knowledge and Early Mobilization in Postoperative Laparatomy Patients in The Inpatient Room RSUD Praya Inpatient Room - Hersika Asmawariza, Lalu (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Surgery is an invasive action (affecting the integrity of body tissue) by opening up parts of the body for repair. (WHO) revealed that the number of patients undergoing surgery from year to year has increased significantly. In 2011 there were 140 million patients in all hospitals in the world, while in 2012 there was an increase of 148 million. The purpose of the study was to determine the relationship between knowledge and mobilization in postoperative laparatomy patients. Method: The research design used in this study was analytic observation. The population amounted to 55 laparatomy patients. The sample was 48 laparatomy patients. The sampling technique was purposive sampling. Data analysis using Chi Square. Result: Based on the results of statistical tests of bivariate analysis using the Chi Square test, the results obtained ρ value = 0.000 <0.05 Based on the rules for rejecting the hypothesis, H0 is rejected, this means and H1 is accepted. Conclusion: There is a relationship between knowledge and early mobilization in postoperative laparatomy patients. This means that the better the patient's knowledge about early mobilization, the more aware the patient is of the importance of early mobilization after laparatomy surgery.